Amorphous mesoporous matrix from metal-organic framework UiO-66 template with strong nucleophile substitution. (April 2021) - Lee, Yu-Jen; Chang, Ying-Ju; Hsu, Jyh-Ping
Abstract: The metal-organic framework (MOF) UiO-66 is made of zirconium clusters coordinated with 1, 4-benzenedicarboxylate linkers that is stable in water and is highly tolerant to extremely acidic or basic environments. Conversely, the zirconium clusters are affine to nucleophiles so the crystalline structures of UiO-66 can be converted into amorphous derivatives. In a mineral acid solution both protons and coordinating nucleophile are present. This study for the first time revealed that it is the strong nucleophile instead of proton deteriorate the crystalline structures of UiO-66. Also, the so-produced amorphous mesoporous matrix, if not totally dissolved, can be applied as an efficient adsorbent. The noted adsorption capabilities of Cu(II) and nucleophiles by these amorphous mesoporous matrix did not correlate with the structural crystallinity or the internal surface area; conversely, the doped nucleophiles were noted to contribute to the adsorption tendencies towards Cu(II) and phosphate species via electrostatic interactions and hydrogen bonding, respectively. Conversion of sacrificing UiO-66 template to amorphous matrix can be applied as an effective way to fabricate specific adsorbent with resistance to extreme pH and strong nucleophile challenges. Highlights: UiO-66 was modified by five nucleophiles at pH 1, 7 and 12. Crystalline structures of UiO-66 were deteriorated with surface area reduced. Nucleophile instead of proton attacks the UiO-66 converting it into amorphous matrix. Amorphous matrix was used for Cu(II) and phosphate adsorption. Interactions between doped nucleophiles and adsorbates determine adsorption capacity.